Accidental Carbon monoxide poisoning with Neurological Sequelae (Bangladesh Critical Care Journal, 2022)
Carbon monoxide (CO) intoxication is one of the leading causes of accidental poisonings1. It often leads to diagnostic errors, because of its presenting symptoms are extremely nonspecific and confounding. Symptoms commonly include headache, dizziness, weakness, vomiting, chest pain and confusion. Large exposures can result in loss of consciousness, arrhythmias, seizures, or death. The most common location of exposures causing CO poisoning are in homes and less commonly in workplaces 2. Unintentional, non-fire related CO poisoning is responsible for approximately 450 deaths and 21,000 emergency department (ED) visits each year in United States3,4,5.Bangladesh Crit Care J March 2022; 10 (1): 75-77